An audit of the dissemination strategies and plan included in international food-based dietary guidelines - Sze Lin Yoong; Heidi Turon; Carrie K Wong; Lyndal Bayles; Meghan Finch; Courtney Barnes; Emma Doherty; Luke Wolfenden (Cambridge University Press, 2023)
Abstract Objective: Food-based dietary guidelines (FBDG) are an important resource to improve population health; however, little is known about the types of strategies to disseminate them. This study sought to describe dissemination strategies and content of dissemination plans that were available for FBDG. Design: A cross-sectional audit of FBDG with a published English-language version sourced from the United Nations FAO repository. We searched for publicly available dissemination strategies and any corresponding plans available in English language. Two authors extracted data on strategies, which were grouped according to the Model for Dissemination Research Framework (including source, audience, channel and message). For guidelines with a dissemination plan, we described goals, audience, strategies and expertise and resources according to the Canadian Institute for Health Research guidance. Setting: FBDG from fifty-three countries mostly from high-income (n 28, 52·8 %), and upper-middle income (n 18, 34 %) areas were included. Participants: n/a. Results: The source of guidelines was most frequently health departments (79·2 %). The message included quantities and types of foods, physical activity recommendations and 88·7 % included summarised versions of main messages. The most common channels were infographics and information booklets, and the main end-users were the public. For twelve countries (22·6 %), we were able to source an English-language dissemination plan, where none met all recommendations outlined by the Canadian Institute for Health Research. Conclusions: The public was the most frequently identified end-user and thus most dissemination strategies and plans focused on this group. Few FBDG had formal dissemination plans and of those there was limited detailed provided.